2016
DOI: 10.1017/s175173111600077x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon stimulated genes as peripheral diagnostic markers of early pregnancy in sheep: a critical assessment

Abstract: We investigated the diagnostic reliability of pregnancy detection using changes in interferon stimulated gene (ISG) messenger RNA (mRNA) levels in circulating immune cells in ewes. Two different groups of ewes (an experimental group, experiment 1 and a farm group, experiment 2) were oestrus-synchronized and blood sampled on day 14 (D0 = day of insemination in control animals, experiment 1) and day 15 (experiment 2). Real-time PCR were performed to evaluate the abundance of different ISG mRNAs. In the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
4
19
1
Order By: Relevance
“…2). These findings were similar to previous results that there were changed expressions of ISG15 in endometrium [3,24] , blood cells [25,26] , CL [6,27] during early pregnancy in sheep and cattle. It was indicated that the embryonic signal (IFNT) reached the blood cells, CL and BM to up-regulate ISG15 expression through blood or/and immune cells during early pregnancy in sheep.…”
Section: Discussionsupporting
confidence: 92%
“…2). These findings were similar to previous results that there were changed expressions of ISG15 in endometrium [3,24] , blood cells [25,26] , CL [6,27] during early pregnancy in sheep and cattle. It was indicated that the embryonic signal (IFNT) reached the blood cells, CL and BM to up-regulate ISG15 expression through blood or/and immune cells during early pregnancy in sheep.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in ISG15 in neutrophils with IFNT supplementation is in agreement with the earlier findings obtained from blood cells in sheep, 16 bone marrow of ewes, 17 and liver biopsies 18 of HF cattle in early pregnancy. The increase in ISG15 in neutrophils with IFNT supplementation is in agreement with the earlier findings obtained from blood cells in sheep, 16 bone marrow of ewes, 17 and liver biopsies 18 of HF cattle in early pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Expression CXCL10 mRNA is upregulated in bovine endometrium and PBLs on days 15 and 18 of pregnancy, and can be induced by IFNT in cultured endometrial tissue or PBLs [38,39]. Early pregnancy induces upregulation of CXCL10 gene in the endometria and PBMCs in sheep [40,41]. CXCL10 mRNA in endometrium and protein in the uterine flushing are increased from day 14 to 20 of pregnancy, which are involved in regulating endometrial functions through recruitment of immune cells in sheep [42].…”
Section: Discussionmentioning
confidence: 99%